2020
DOI: 10.1111/gbb.12695
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between touchscreen operant chambers and water maze to detect early prefrontal dysfunction in mice

Abstract: The relative lack of sensitive and clinically valid tests of rodent behavior might be one of the reasons for the limited success of the clinical translation of preclinical Alzheimer's disease (AD) research findings. There is a general interest in innovative behavioral methodology, and protocols have been proposed for touchscreen operant chambers that might be superior to existing cognitive assessment methods. We assessed and analyzed touchscreen performance in several novel ways to examine the possible occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Additionally, reversal learning tasks have been sensitive to cognitive flexibility impairments in AD mouse models as they age ( Piiponniemi et al, 2017 ; Shepherd et al, 2019 ; Van den Broeck et al, 2019 ) and attention and executive control have also been scrutinized and shown to be sensitive to donepezil ( Romberg et al, 2011 ), a drug commonly used clinically for AD. Recently, Van den Broeck et al (2021) showed that touchscreen tests were more sensitive in picking up memory impairments in an AD model compared to traditional maze-based tests. Although this is promising for early detection of impairments, and thus insight into early disease mechanisms, not all studies have shown early detection of impairments, with one reporting no differences in aged mice expressing a mutation in Tau ( Kent et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, reversal learning tasks have been sensitive to cognitive flexibility impairments in AD mouse models as they age ( Piiponniemi et al, 2017 ; Shepherd et al, 2019 ; Van den Broeck et al, 2019 ) and attention and executive control have also been scrutinized and shown to be sensitive to donepezil ( Romberg et al, 2011 ), a drug commonly used clinically for AD. Recently, Van den Broeck et al (2021) showed that touchscreen tests were more sensitive in picking up memory impairments in an AD model compared to traditional maze-based tests. Although this is promising for early detection of impairments, and thus insight into early disease mechanisms, not all studies have shown early detection of impairments, with one reporting no differences in aged mice expressing a mutation in Tau ( Kent et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the F8M procedure described here, touchscreen tasks minimize stress, allow for a high degree of automation and standardization, and thus facilitate longitudinal testing. In addition, they have been successfully used to detect early cognitive deficits starting at 3 moa in APP/PS1-21 mice ( Van den Broeck et al, 2021 ), suggesting higher sensitivity than the DAT. The preferred use of different procedures will depend on the aim of the study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to representing a welfare concern, the stress induced by this task can interfere with the interpretation of results and animal performance 83,84 . Two independent studies compared the performance of two Alzheimer's mouse models (APP-KI and APP/PS1) on the MWM to the performance of touchscreen PAL, location discrimination (LD) and visual discrimination and reversal tasks; these studies reported that the touchscreen tasks detected significant performance impairments in the model animals compared to wild-type controls at an earlier age (and so under conditions of lesser pathological burden) than the MWM 52,85 . These findings suggest that the touchscreen approach can offer higher sensitivity assessment with lower stressor exposure, consistent with a substantial refinement.…”
Section: Refinementmentioning
confidence: 99%
“…More importantly, these assays have persistent negative effects on animal welfare 140,141 . In addition, given the increased sensitivity of touchscreen tasks relative to the MWM 52,85 , in which animals are also exposed to stress, touchscreen tasks might also show enhanced sensitivity compared to FST and TST, although to our knowledge this important comparison remains to be completed.…”
Section: Exemplar Applications Of Touchscreen Techniquesmentioning
confidence: 99%